ANALYSIS MODEL AND FINANCIAL DYNAMICS IN CASH MANAGEMENT IN ASRO INDONESIA NAVAL TECHNOLOGY COLLEGE POSTGRADUATE STUDENTS - Yoyok Nurkaya Santosa; Radityo Dimas; Yos Aru Moreta (JOURNAL ASRO, 2022)
Financial management is an activity to organize, planning, directing, and supervising financial activities Financial management is crucial in maintaining the sustainability of an institution or company to achieve its goals. Financial policies are taken to achieve effective and efficient use of the budget in planning, implementing and managing an activity that aims to achieve optimal profit. Likewise, with ASRO STTAL postgraduate students facing the dynamics of education courses require proper financial management so that budgetary support during the education process can be managed and utilized appropriately. By using a dynamic system, this study investigates the impact of scenarios on the internal financial policy of ASRO IX students on the financial dynamics of the cash flows of ASRO IX STTAL students. The scenarios were developed into optimistic, moderate and pessimistic scenarios. The Pessimistic Scenario shows results with stable financial dynamics which results in an increase in the amount of cash at the best of 71.3%. Simulation The policy scenario generates total cash at the end of the education period of Rp. 23,616.117. The model building can be used as a financial policy analysis tool for STTAL students. Keywords: Financial Management, Policy, System Dynamic